The Mandarin Language Training for Business to Enhance Vocational Student Competitiveness in the Global Era - Siregar, Sheyla Silvia; Nursafitri , Sintia; Rehatta, Stanny Dewanty (Majalah Ilmiah UPI YPTK, 2025)
Vocational high school (SMK) students, as future skilled workers, still face challenges in global communication skills, particularly in Business Mandarin. This limitation hinders their ability to meet the demands of industries increasingly engaged in cooperation with Chinese companies. The urgency of Business Mandarin training lies in the growing need for a workforce that not only possesses technical expertise but can also communicate effectively in multicultural environments. Proficiency in Business Mandarin serves as a significant competitive advantage for SMK graduates, enhancing their employability in the global labor market. The Business Mandarin and CV Writing Training Program aims to equip students with practical business communication skills and professional CV writing abilities. This program is expected to strengthen the competitiveness of SMK graduates while bridging the gap between education and industry needs in the Industry 5.0 era.